Understanding Islam and the Muslims expanded to include the Muslim family and Islam and world peace - Winter, T. J.; Williams, John A. (Louisville, Ky. Fons Vitae, 2002)
Myths and misunderstandings continue to proliferate about Islam and its millions of followers worldwide. To refute these misconceptions, this newly-expanded, magnificently illustrated version offers succinct, and sometimes surprising, answers to the frequent questions about the Muslim faith in an accessible question and answer format.
Keywords: Islam -- 20th century; Muslims -- 20th century